ANALISIS FRAMING PEMBERITAAN ISU PENCABULAN SANTRIWATI DI SERANG BANTEN PADA KOMPAS.COM DAN TRIBUNBANTEN.COM - Nanda Kumala Haryanti; Anwari (Spektra Komunika : Jurnal Komunikasi & Dakwah, 2023)
This study focuses on two issues: firstly, how Kompas.com conducts the framing of news regarding the case of three female Islamic boarding school students' molestation in Kasemen District, Serang City, Banten, on December 12, 2022, and secondly, the comparison of news framing regarding the same molestation case between Kompas.com and TribunBanten.com on December 12, 2022. To address these two issues, the researcher utilizes a qualitative approach. The method employed by the researcher is the framing analysis method developed by Robert N. Entman in the study entitled “Framing the Issue of Female Islamic Boarding School Students' Molestation in the Online Media of Kompas.com and TribunBanten.com on December 12, 2022. The findings of this study lead to the conclusion that Kompas.com and TribunBanten.com exhibit distinct textual structures. Particularly on Kompas.com, there is a discernible tendency to side with the victims and firmly incriminate the perpetrators. On the other hand, the textual structure of news regarding the issue of Female Islamic Boarding School Students' Molestation on TribunBanten.com demonstrates a lack of clarity in delineating the chronology of events. Moreover, the discourse accentuates the notion that the conduct undertaken by the perpetrators is inherently unacceptable and should not have transpired.